(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Neonatal infection with SARS‑CoV‑2 is rare, but in cases of vertical or perinatal transmission, lung pathology may reflect characteristic morphological and immune alterations. We review available case reports and autopsy studies of neonates born to COVID‑19 positive mothers, focusing on histopathology, immunohistochemistry, and ultrastructural findings of pulmonary tissue. Key findings include diffuse alveolar damage (DAD), type II pneumocyte hyperplasia, interstitial mononuclear infiltration, macrophage accumulation, and variable expression of immune cell markers (CD68, CD4, CD8, FOXP3, IL‑6, IL‑17). We highlight limitations in the current literature, propose a schematic histologic/immunohistochemical table, and suggest directions for future systematic studies.